Excessive Polypharmacy Among Indonesian Heart Failure Patients: Clinical Correlates and Care Implications - Yogi Puji Rachmawan; Witri Pratiwi; Bambang Budi Siswanto (Jurnal Kardiologi Indonesia, 2026)
Background: Heart Failure (HF) is a major global health problem that often coexists with multiple chronic comorbidities, requiring complex pharmacotherapy. The use of numerous concurrent medications increases the risk of polypharmacy and excessive polypharmacy, which may lead to adverse drug reactions, drug–drug interactions, poor adherence, and higher healthcare utilization. Despite growing awareness of this issue, evidence on the prevalence and determinants of excessive polypharmacy among Indonesian HF patients remains scarce. Methods: This single-center cross-sectional sub-analysis was derived from a cross-sectional study involving 494 adult HF patients treated at Hasna Medika Cardiovascular Hospital, Cirebon, between January and December 2023. HF diagnosis was confirmed by cardiologists using the European Society of Cardiology (ESC) criteria. Polypharmacy was defined as the use of ≥7 medications, while excessive polypharmacy was defined as ≥10 medications. Clinical and demographic variables were extracted from electronic medical records (EMR). Bivariate analysis was performed using Chi-square or Fisher’s exact tests, followed by multivariate logistic regression to identify independent determinants of excessive polypharmacy. Results: The mean age of participants was 58.1 ± 10.5 years, and 53.4% were male. Overall, 42.5% of patients met the criteria for polypharmacy, and 15.6% (n=77) met the criteria for excessive polypharmacy. The most frequent comorbidities were Coronary Artery Disease (CAD) (80.2%), hypertension (23.1%), and Type 2 Diabetes Mellitus (T2DM, 20.0%). In multivariate analysis, T2DM (Adjusted Odds Ratio [AOR] 17.21, 95% CI 8.39–35.34), Chronic Kidney Disease (CKD) (AOR 5.97, 95% CI 2.37–15.03), Chronic Obstructive Pulmonary Disease (COPD) (AOR 6.64, 95% CI 2.64–16.69), and asthma (AOR 26.32, 95% CI 5.79–119.67) were identified as independent determinants of excessive polypharmacy. The model demonstrated good fit (McFadden pseudo-R² = 0.351; Hosmer–Lemeshow p = 0.62). Conclusion: Excessive medication burden is common among HF patients, particularly among those with metabolic and pulmonary comorbidities. These findings highlight the need for systematic medication review and rational prescribing strategies while recognizing that higher medication counts do not necessarily indicate inappropriate prescribing.